2004
DOI: 10.1152/jn.00352.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Epidermal Growth Factor in Rat Brain Extracellular Space Measured by Integrative Optical Imaging

Abstract: Diffusion of epidermal growth factor in rat brain extracellular space measured by integrative optical imaging. J Neurophysiol 92: 3471-3481, 2004. First published July 21, 2004 doi:10.1152/jn. 00352.2004. Epidermal growth factor (EGF) stimulates proliferation, process outgrowth, and survival in the CNS. Understanding the actions of EGF necessitates characterizing its distribution in brain tissue following drug delivery or release from cellular sources. We used the integrative optical imaging (IOI) method to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 63 publications
11
132
0
Order By: Relevance
“…Epidermal growth factor possesses a low tortuosity (l) value of 1.8 and this low resistance to migration may cause the elevated T 2 value as seen at the early time point of 24 hours. 40 Eight times heavier than EGF, PEDF might have induced a rather persistent elevation in T 2 values as observed with this group. As the core body temperatures of all animals were maintained at 37.5-37.7 1C any influence of temperature on T 2 values may be safely ruled out.…”
Section: Effect Of Epidermal Growth Factor and Pigment Epitheliumderisupporting
confidence: 62%
“…Epidermal growth factor possesses a low tortuosity (l) value of 1.8 and this low resistance to migration may cause the elevated T 2 value as seen at the early time point of 24 hours. 40 Eight times heavier than EGF, PEDF might have induced a rather persistent elevation in T 2 values as observed with this group. As the core body temperatures of all animals were maintained at 37.5-37.7 1C any influence of temperature on T 2 values may be safely ruled out.…”
Section: Effect Of Epidermal Growth Factor and Pigment Epitheliumderisupporting
confidence: 62%
“…The diffusion of EGF in the brain has been estimated to be 5x10 -7 cm 2 /s [Thorne et al 2004] which is equivalent to approximately 0.05 cm/hour; therefore d can be estimated to be approximately 25 to 50 if we assume that the size of a cell is 10-20µm. Thorne et al 2004 actually calculate the diffusion range of EGF; using the curve shown in their Fig.…”
Section: Estimating the Parametersmentioning
confidence: 99%
“…The diffusion of EGF in the brain has been estimated to be 5x10 -7 cm 2 /s [Thorne et al 2004] which is equivalent to approximately 0.05 cm/hour; therefore d can be estimated to be approximately 25 to 50 if we assume that the size of a cell is 10-20µm. Thorne et al 2004 actually calculate the diffusion range of EGF; using the curve shown in their Fig. 6, the diffusion range at which the concentration of the growth factor is 50% of the concentration at the source is between 100 and 600 µm, that is (assuming again that cell size is between 10 and 20 µm), d=5-10 to 30-60.…”
Section: Estimating the Parametersmentioning
confidence: 99%
“…Fluorochrome-labeled epidermal growth factor (EGF) has been a versatile tumor imaging agent because the epidermal growth factor receptor (EGFR) is overexpressed on the surface of many types of tumor cells [20], [21], [22], [23], and [24]. In a study measuring the diffusion of small molecules across the extracellular space in rat brains, Thorne et al [25] showed that EGF labeled with Oregon green 514 could be used as a reporter. Ke et al [26] used Cy5.5-labeled EGF to target human breast tumor cells implanted in mice.…”
Section: Tumor Surface Proteinsmentioning
confidence: 99%